The Influence of Hedonic Shopping Motivation and Electronic Word of Mouth (eWOM) on Impulse Buying in Shopee E-Commerce Users in Medan Tuntungan with Positive Emotion as an Intervening Variable - Wulanda, Astrea; Rini, Endang Sulistya; Sembiring, Beby Karina Fawzeea (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to determine and analyze the effect of hedonic shopping motivation and electronic word of mouth on impulse buying through positive emotion in Shopee users. This type of research is associative research using quantitative data The sampling technique used was purposive sampling with the criteria that respondents who have shopped at Shopee for at least a year. The data were analyzed using the Structural Equation Modeling method with the Smart PLS version 4.0 analysis tool. The results showed that directly hedonic shopping motivation has a positive and significant effect on positive emotion and impulse buying, electronic word of mouth has a positive and insignificant effect on positive emotion and impulse buying, positive emotion has a positive and significant effect on impulse buying. In indirect research results, hedonic shopping motivation has a positive and significant effect on impulse buying through positive emotion. Meanwhile, electronic word of mouth has a positive and insignificant effect on impulse buying through positive emotion.